Lifetime thermal analysis of the CANDU spent fuel storage canister at the Wolsung site - Tae Gang Lee; Taehyung Na; Byongjo Yun; Jae Jun Jeong (Nuclear Engineering and Technology)
CANDU spent fuels in the Wolsung site have been stored in dry storage systems, such as concrete canisters and modular air-cooled storage system. The primary role of the canister is to ensure the integrity of the fuel during the storage period, which is significantly influenced by temperature. Thus, thermal analysis for the canister's components, especially for fuel cladding, is essential to demonstrate its safety. The thermal analysis has been conducted mainly for predicting the peak cladding temperature (PCT) since high temperature of the fuel can promote oxidation and cracking. As the expiration of storage license approaches, fuel transfer to final disposal should be prepared. This also requires a thermal analysis to predict minimum cladding temperature (MCT), which is related with brittleness. So, it is crucial to accurately predict both PCT and MCT during entire storage period. The cladding temperature is primarily influenced by decay heat and ambient conditions. The lifetime PCT may occur during summer at the beginning of storage, while the lifetime MCT occurs during winter at the end of storage. In this study, we calculated the PCT and MCT during the entire storage period using a realistic thermal analysis model and, subsequently, conducted their uncertainty analysis.